PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA PADA MATA PELAJARAN PAI DAN BUDI PEKERTI DI KELAS VIIA SMP NEGERI 1 SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Maya Helmita; Zulhaini Zulhaini; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
The background of this research is based on the problems that occur in class VII A at SMP Negeri 1 Singingi downstream, Kuantan Singingi Regency which shows less than the maximum. The value of students in PAI and Budi Pekerti subjects is still low. This is because PAI and Budi Pekerti learning is a broad subject, with lots of material, in the form of writing, memorizing, and even learning that is monotonous with only lectures. In the learning process, students do not get an interesting impression from the process of the learning activities. Based on the above background, the formula for this research is how to increase students' learning motivation in PAI and Budi Pekerti subjects with the material All clean, life becomes comfortable by using the Picture And Picture learning model. This study aims to increase students' learning motivation in PAI subjects and in class VII A of SMP Negeri 1 Singingi Hilir, Kuantan Singingi Regency by applying the Picture And Picture learning model. In this study, researchers used classroom action research methods. The results showed that the completeness of learning based on the KKM with learning from the results of the pre-cycle to the second cycle with the number of different values. Based on the results of the pre-cycle, the values are 723: 3,300 x 100 = 21.9% which have not been applied, while the values that have been applied are 267: 3,300 x 100 = 8.0%. While the first cycle that has applied with a value of 484: 3,300 x 100 = 14.6%, while those who have implemented it with a value of 402: 3,300 x 100 = 12.2%. Then it increased in the second cycle with a value of 618: 3,300 x 100 = 18.7 who had implemented it, while the number of values that had not applied was 378: 3,300 x 100 = 11.4%. Thus it can be concluded that the Picture And Picture learning model in increasing the value of learning motivation increases the activeness of students in asking and answering. Recommendations are given to teachers, principals, and future researchers.